Frequently misdiagnosed condition can be identified earlier by looking at phenotypic features - Khalid, Ahmed Murtaz (Journal of University Medical & Dental College, 2025)
Diabetes is a global epidemic affecting the quality of life of patients and their families. It doesn’t come alone, however opens the door of complications i.e. cardiovascular comorbidity. LADA (Latent autoimmune diabetes of adults) is a type responding to oral medication initially however there is unavoidable complete beta cell burn out in the years to come and time period does vary. Adhering to insulin sensitizers and avoiding sulphonyl urea might slow down the complete exhaustion of beta cells in these patients. Many a time’s poor blood glucose control in these patients is related to poor medication or dietary compliance, delaying the start of insulin. Instead primary healthcare physician needs to be aware of the phenotypic features (thin and lean patient in their 40s) of the LADA to identify the inevitable complete beta cell burn out requiring insulin at earlier stage in order to avoid complications.